1989
DOI: 10.1111/j.1469-8137.1989.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon partitioning patterns of mycorrhizal versus non‐mycorrhizal plants: real‐time dynamic measurements using 11CO2

Abstract: S U M M A K ^•Oas exchnnj^e and c;irl">on ;illoc:ition piilterns were sttidied in two popiihitums of I'diiictiiii rolorotiiiii, :in .Mrica C-4 grass. The pUints were grown ni split-root pots, eontammg partially sterihzed soil, with one side either inoculated (I) or not inoculated (NI) with a \-esieuliir-iirbuscuhir (\'.A) ni\ corrliizal fungus, (iigaspora margarita. Net carbon exchange rates (CER) and stomatal conductances were measured with conventional gas exchange apparatus, and carbon assimilation, translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…The additional amount of CO 2 respired by M compared with NM root systems as a percentage of the net amount of CO 2 assimilated by M plants was 15% on day 42. This is in good agreement with previous studies which have shown that the additional amount of 14 C respired by roots of 14 CO 2 -labelled M plants ranged from 4 to 20% of the total net CO 2 fixed by the plant (Pang & Paul 1980;Paul & Kucey 1981;Kucey & Paul 1982;Snellgrove et al 1982;Koch & Johnson 1984;Harris et al 1985;Douds et al 1988;Wang et al 1989).…”
Section: Figuresupporting
confidence: 82%
See 2 more Smart Citations
“…The additional amount of CO 2 respired by M compared with NM root systems as a percentage of the net amount of CO 2 assimilated by M plants was 15% on day 42. This is in good agreement with previous studies which have shown that the additional amount of 14 C respired by roots of 14 CO 2 -labelled M plants ranged from 4 to 20% of the total net CO 2 fixed by the plant (Pang & Paul 1980;Paul & Kucey 1981;Kucey & Paul 1982;Snellgrove et al 1982;Koch & Johnson 1984;Harris et al 1985;Douds et al 1988;Wang et al 1989).…”
Section: Figuresupporting
confidence: 82%
“…The additional amount of CO 2 respired by M compared with NM root systems as a percentage of the net amount of CO 2 assimilated by M plants was 15% on day 42. This is in good agreement with previous studies which have shown that the additional amount of 14 C respired by roots of 14 CO 2 -labelled M plants ranged from 4 to 20% of the total net CO 2 fixed by the plant (Pang & Paul 1980;Paul & Kucey 1981;Kucey & Paul 1982;Snellgrove et al 1982;Koch & Johnson 1984;Harris et al 1985;Douds et al 1988;Wang et al 1989).By day 53, that the C budgets were still significantly different between M and NM plants when expressed on a per plant basis, could be attributed to the fact that M plants had, for the first time, become significantly larger than those in the NM condition. The fact that the growth of M plants did eventually outpace that of plants grown in the NM condition could indicate that the superior potential for nutrient capture was eventually expressed in colonized plants and may have masked any sink effects.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This will probably affect the availability-of photoassimilate for fungal metabolism. Root systems colonized by VA mycorrhiza] fungi acquire a greater percentage of photoassimilate than non-mycorrhizal roots (Koch & Johnson, 1984;Douds, Johnson & Koch, 1988;Wang et al, 1989). In our study there was a tendency for mycorrhizal plants to have a greater proportion of ^*C in the roots compared with non-mycorrhizal plants (Table 3).…”
Section: Discussionsupporting
confidence: 48%
“…notatuni and Agrostis stolonifera act as an important sink for sucrose, converting it rapidly into sugar alcohols (Thrower & Lewis, 1973;Smith, Bacon & Luttrell, 1985). A strong sink for photosynthates might reduce or prevent feedback inhibition of photosynthetic rates, thereby' allowing higher average growth rates (Wang et al, 1989;Lyons, Evans & Bacon, 1990;Larson & Whitham, 1991).…”
Section: Discussionmentioning
confidence: 99%